2018
DOI: 10.18203/2320-1770.ijrcog20184923
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on neonatal outcome of preterm births and associated factors in a South Indian tertiary hospital setting

Abstract: Background: In spite of the manifold advances in obstetric care, preterm births are still a nightmare for the obstetrician, the pregnant women and her family. The present study aims to study the neonatal outcome in preterm births and its association with sociodemographic, medical and obstetric risk factors.Methods: A prospective observational study done in the Department of Obstetrics and Gynecology in a tertiary level hospital in South India for a period of two years.Results: Majority of the preterm births in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…4 observed majority of the women in both groups of preterm and term labor were between 20-29 years which is similar to present study. Philip et al 5 in their study on neonatal outcome of preterm births found no significant association of the maternal age to the neonatal outcome in preterm births in present study which is similar to present study. Following table shows mean age in different studies [3][4][5] .…”
Section: Table Iii: Distribution Of Pre-term Cases According To Postn...supporting
confidence: 90%
See 1 more Smart Citation
“…4 observed majority of the women in both groups of preterm and term labor were between 20-29 years which is similar to present study. Philip et al 5 in their study on neonatal outcome of preterm births found no significant association of the maternal age to the neonatal outcome in preterm births in present study which is similar to present study. Following table shows mean age in different studies [3][4][5] .…”
Section: Table Iii: Distribution Of Pre-term Cases According To Postn...supporting
confidence: 90%
“…Philip et al 5 in their study on neonatal outcome of preterm births found no significant association of the maternal age to the neonatal outcome in preterm births in present study which is similar to present study. Following table shows mean age in different studies [3][4][5] . In present study, majority 32(64%) of study subjects were primigravida followed by 15 (30%) having multigravida.…”
Section: Table Iii: Distribution Of Pre-term Cases According To Postn...supporting
confidence: 90%
“…10 The rate of live birth in present study was 89.33%, early neonatal death rate was 6.6% and the fresh still birth rate was 4% which is similar to study done by Philip et al in which live birth rate was 84%. 5 In my study, amongst 75 preterm birth, 60% neonates developed complications, majority was respiratory distress syndrome (18.6%), neonatal hypoglycemia (16%), sepsis (4%), narcotising enterocolitis (4%) and encephalitis (2%). Garg et al observed 84% of neonates requiring NICU admission with complications of jaundice in (30%) of neonates followed by asphyxia (18%) and RDS (16%).…”
Section: Distribution Of Subjects According To Fetal Complicatiosmentioning
confidence: 69%
“…3 According to WHO if the delivery is occurring after the period of viability and before completing 37 weeks of gestation or 259 days since the first day of women's Last menstrual period than it is defined as preterm labour. 4 We classify preterm deliveries into two main groups. One is the delivery occurring after 28 weeks of gestation but before completing 34 weeks than it is known as early preterm and the other is delivery occurring after 34 weeks but before completing 37 weeks of gestation than it is known as late preterm.…”
Section: Introductionmentioning
confidence: 99%